Regulating human stem cell research and therapy in low- and middle-income countries: Malaysian perspectives - Abdul Aziz, Mohammad Firdaus; Morrison, Michael; Kaye, Jane (Taylor & Francis, 2018)
Many “rising powers” such as India, China, Argentina, Singapore, and Brazil are investing in stem cell technology, joining the traditional leaders in the field, such as the UK, Germany, USA, and Japan. Malaysia is also entering this sector because of the potential medical and economic benefits that the use of stem cell technologies could provide. Like other countries, Malaysia faces the challenge of how to encourage scientific progress and innovation in an ethical manner while at the same time ensuring a safe and accessible market for regenerative therapies. This paper reports on the research findings of semi-structured interviews with local stakeholders to investigate how they perceived and evaluated the current regulatory framework for human stem cell research in Malaysia, and what might be at stake if the state continues with its current regulatory approach.